Motivaciones y barreras para realizarse una prueba de detección de VIH en hombres que tienen sexo con hombres - Diaz Vera, Arnold Andree (2016)
HIV testing is one of the pillars in the control of the disease, however key populations such as the MSM population do not perform it regularly, reports indicate that only 7% of this population performs one test annually in our country. Objective: To know the motivations and barriers that influence the performance of an HIV test in MSM patients. Materials and Methods: Descriptive, cross-sectional and prospective study. During the period April - September 2016, questionnaires were applied to the MSM patients who attended the CERITS of the HRDT, socio-demographic characteristics were collected and the acceptance of a list of 11 motivations and 15 barriers was evaluated. Results: 105 questionnaires were collected; the most accepted motivations were 'I want to check my health' followed by 'I would like to know if I am HIV positive'; The main barriers were ‘I am afraid of the consequences of a positive test result' and ‘A positive result would turn my life upside down'. Conclusion: The main motivation was 'I want to check my health' and the main barrier was I am afraid of the consequences of a positive test result'